The alchemist : A Fable about following your dream - Coelho, Paulo (London : Harper, 2012)
Santiago, an Andalusian shepherd boy, sets out from his home in Spain to the Egyptian desert in search of buried treasure, but through his encounters with a Gypsy woman, a man who calls himself a king, and an Alchemist, he learns the value of the treasure found within himself.
Adult.
Adult
Keywords: Alchemists -- Fiction; Self-realization -- Fiction; Shepherds -- Fiction; Alchemists -- Fiction; Fables; Self-realization -- Fiction; Shepherds -- Fiction; Egypt -- Fiction; Spain -- Fiction; Egypt -- Fiction; Spain -- Fiction